Blood and circuses [compact disc, unabridged] : a Phryne Fisher mystery - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery., 2011)
The Honorable Miss Phryne Fisher is feeling dull. But is she bored enough to leave her identity, home and family behind and join Farrell's Circus and Wild Beast Show? There have been strange things happening at the circus. And when Phryne is asked by her friends, Samson the Strong Man, Alan the carousel operator and Doreen the Snake Woman, to help them, curiosity gets the better of her.